Heterogeneous pattern of improvement in right ventricular mechanics following hematopoietic stem cell transplant in patients with systemic sclerosis. (8th February 2021) - Chen, C; Nishtala, A; Groenendyk, JW; Schultz, WM; Li, E; Shah, SJ; Burt, RK; Freed, BH
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Systemic sclerosis (SSc) is an autoimmune disorder that causes fibrosis in the skin and internal organs, including the heart. Patients with SSc can have right ventricular (RV) systolic dysfunction in the absence of pulmonary hypertension. Studies have shown a predilection for impairment of the mid and apical segments of the RV free wall compared to controls. The effect of hematopoietic stem cell transplant (HSCT) – a disease modifying treatment for SSc – on RV mechanics is not known. Aim: To study the effect of HSCT on RV mechanics using speckle-tracking echocardiography. Methods: Patients with SSc who underwent comprehensive 2D echocardiographic evaluation pre- and post-HSCT were identified. The modified Rodnan skin score (mRSS) was evaluated for each patient pre- and post-HSCT. Speckle tracking software was utilized to measure myocardial strain (TomTec, Unterschleissheim, Germany). RV strain was measured from the RV focused apical 4-chamber view. Paired student's t-test and linear regression analysis were used in data analysis. Results: Among 89 patients with SSc (average age 46 ± 11 years, 75% female) who underwent HSCT, the mRSS significantly improved after HSCT. The mean pulmonary arterial pressure measured by right heart catheterization prior to HSCT was 18.5 ± 4.5 mmHg. There was a significant improvement in RV global longitudinal strain (GLS) and free wall strain (FWS) following HSCT. The improvement in strain was significant in the mid and apical segments of the RV free wall, but not so in the basal segment. The change in RV strain was linearly related to pre-HSCT strain. The lower the RV GLS and FWS, the greater the improvement in strain after HSCT. Conclusions: There was a significant improvement in RV strain in patients undergoing HSCT, specifically within the mid and apical segments of the RV free wall. The improvement in strain after HSCT was directly related to the baseline strain. This suggests that HSCT may directly improve RV mechanics with the preferential enhancement of the less robust mid and apical RV free wall segments.